Challenges of Science 2019
DOI: 10.31643/2019.004
|View full text |Cite
|
Sign up to set email alerts
|

Intersubjective Management in Educational Economy

Abstract: The modern economy, the management of its development, is one of the most actively developing aspects of the life of the community, closely related to others (cultural and ideological, political and historical, psychological and legal transformations.) Recently, researchers are seeking answers to questions of optimizing the development of the economy in theories and technologies not only monoagent and multi-agent control, but monoactor and multi-agent, quality and quantity management, logistics and production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…Mathematical skills are great of importance to be developed at a school; the modern economy, the management of its development, is one of the most actively developing aspects of the life of the community (Arpentieva et al, 2019). Based on the results of students' work in completing two-variable linear equation problems found that it is necessary to have learning trajectory, so that students will be easier in learning the concept of twovariable linear equation.…”
mentioning
confidence: 99%
“…Mathematical skills are great of importance to be developed at a school; the modern economy, the management of its development, is one of the most actively developing aspects of the life of the community (Arpentieva et al, 2019). Based on the results of students' work in completing two-variable linear equation problems found that it is necessary to have learning trajectory, so that students will be easier in learning the concept of twovariable linear equation.…”
mentioning
confidence: 99%
“…Its peculiarity is manifested in the weakening of control by the frontal regions of the hemispheres of the temporal zones, which are closely associated with the emotion-generating limbic system. However, it is worth mentioning once again that such a comparison can only be carried out without taking into account the signs of a cognitive and emotional-volitional defect arising from the procedural-progressive course of mental disorders (Merrin, Floyd & Fein, 1989;Norman et al, 1997;Arpentieva et al, 2019;Strelets, Novototskiy-Vlasov, & Golikova, 2001;Nerobokova et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The main condition is not to prevent them from fulfilling their duties, overloading their lives with the need to deal with quasi-business issues, which are actively imposed in the process of trade in "educational services" to the detriment of the practice of training and education as a process of socio-cultural reproduction and development of society. Thus, the innovative potential of a nation depends not only on individual participants in the innovation system (companies, universities, government), but, more importantly, on the links between these players and on educational system, personal development (Arpentieva et al, 2019). Delivery of education should be connected with the real industry workforce and applied science.…”
Section: Issn 1991-3494mentioning
confidence: 99%